Exploring the Long-Term Relationship Between Thermospheric ∑O/N2 and Solar EUV Flux - Hao Li; Cunying Xiao; Kuan Li; Zewei Wang; Xiaoqi Wu; Yang Yu; Luo Xiao (Remote Sensing)
Column O/N2 ratio (∑O/N2), a physical quantity representing thermospheric disturbances, is influenced by solar extreme ultraviolet radiation flux (QEUV) changes. Investigating the correlation between these two factors is essential for understanding the evolution of the thermosphere. This study examines the correlation and periodic variations of ∑O/N2 and QEUV across different phases of solar activity, using data from the Global Ultraviolet Imager (GUVI) spanning from 2002 to 2022. A correlation analysis reveals a positive relationship between ∑O/N2 and QEUV. The function fitting results show that the magnitude of changes in ∑O/N2 due to QEUV variations is approximately 30% of the mean ∑O/N2. A wavelet analysis reveals their coherence in periodic components of 27-day, annual, and 11-year periods. These results are significant for studying the Sun–Earth coupling mechanism and understanding the impact of space weather on the thermosphere.